Platelet Adhesiveness and Fibrinolysis after Recent Cerebro-Vascular Accidents and their Relationship with Subsequent Deep Venous Thrombosis of the Legs - Warlow, C. P; Rennie, J. A. N; Ogston, D; Douglas, A. S (Thrombosis and Haemostasis, 1976)
In fifteen patients with a cerebro-vascular accident resulting in an acute hemiplegia there was a subsequent rise in the platelet count and plasma fibrinogen level. There were no significant alterations in platelet adhesiveness, plasminogen activator, plasminogen, FR-antigen and haematocrit. Patients diagnosed as developing deep venous thrombosis with the 125I-fibrinogen technique had a significantly lower platelet adhesiveness and plasminogen level than those who were not.